Congenital Facial Palsy - J Gordon Millichap (Pediatric Neurology Briefs, 1996)
The association between permanent congenital facial palsy in 61 children and recognized risk factors for traumatic birth was investigated in a retrospective case control study at the Departments of Plastic Surgery, Mount Vernon Hospital, Northwood, Middlesex, and the Hospital for Sick Children, Great Ormond Street, London, UK.